Patient-specific biomedical condition monitoring in post-operative cancer patients - Clifton, D; Clifton, L; Tarassenko, L; Watkinson, P; Barber, V; Salmon, J (British Institute of Non-Destructive Testing, 2009)
Large numbers of preventable deaths occur in hospitals each year, due to adverse events such as cardiac arrest and unplanned admission into Intensive Care Units (ICUs) from other hospital wards. The majority of these patients exhibit physiological deterioration in their vital signs prior to onset of the adverse event, which can be detected by condition monitoring. This paper describes a multivariate, multimodal approach to condition monitoring that may be performed in real-time, which has been previously shown to provide early warning of patient deterioration, while generating a small number of false alarms. We describe a clinical trial currently being undertaken in which post-operative cancer patients are monitored in bed for the first day of their recovery period, and then monitored using telemetry for the remainder of their stay in hospital, during which they may be ambulatory. The use of such telemetry requires monitoring techniques that are robust in the presence of signal artefact introduced by patient movement. We also motivate the use of a patient-specific approach to condition monitoring for improved identification of physiological deterioration.